Consumption of crucian carp (Carassius carassius L., 1758) by restocked pike (Esox lucius L., 1758) in a lake with frequent winter hypoxia. (24th August 2013) - Lappalainen, J.; Vinni, M.; Malinen, T.
Summary To assess the effects of stocked pike (Esox lucius L.) on crucian carp (Carassius carassius L.) biomasses, the annual consumption of pike was estimated and compared with removal fishery catches. The studied lake, Lake Savijärvi, is a small (40 ha), shallow and eutrophicated lake in southern Finland with frequent algal blooms during summers and fish kills during winters. Until the 1980s, the fish fauna consisted of pike, perch (Perca fluviatilis L.), roach [Rutilus rutilus (L.)], crucian carp, and tench (Tinca tinca L.). Since 2003, when crucian carp were abundant in the extreme and with only a few roach and tench individuals, the lake has been biomanipulated by removal seining. To enhance the effects of seining, piscivorous pike were restocked in the spring of 2008. During the 3‐year study, the catch of crucian carp decreased from 243 to 136 kg while the catch of pike increased from 0.1 to 5.7 kg per seining hectare due to their spawning in the lake as of 2009. The total crucian carp consumption by captured pike was 588 kg during the 2008–2010 study period. When applying the number of pike estimated with the mark‐recapture method, consumption estimate increased to 917 kg, or 22.9 kg per lake hectare in 2010. Thus, pike consumption of crucian carp was about 17% of the removal catch in 2010.